Regulations Concerning Noise Exposure and Individual Methods of Protection - Ilgurel, Nuri (GALENOS YAYINCILIK, 2013)
Although noise characteristics in industrial facilities vary according to the type of production, high noise levels are usually common. Noise control in industrial facilities is not only significant from the workers' health point of view but also from other points of view such as production efficiency and occupational safety. The most effective way to control noise usually involves controlling it at its source. If this is not sufficient or is impossible, attention should turn to the noise propagation pathway. If noise cannot be sufficiently reduced at its source or along its propagation pathway, then the receiver should take precautions. This study investigated the legal consequences of Turkey's Noise Regulation, which aims to protect industrial workers in noisy environments from the hazardous effects of noise. It mainly covers topics related to individual methods of protection against industrial noise such as the limitation of working hours according to noise exposure and the use of hearing protectors.
Keywords: Noise-induced hearing loss; ear protectors; ear muffs; ear plugs; noise regulation in Turkey; physiological and psychological effects of noise; Otorhinolaryngology